DETERMINING FACTORS INFLUENCING THE INTENTION TO SWITCH FROM CONVENTIONAL BANKS TO ISLAMIC BANKS USING A MIXED-METHODS APPROACH - Amalia Nuril Hidayati; Vida Maria Ulfa; Mohammad Robet Abdillah (UIN Sunan Gunung Djati Bandung, 2026)
This study examines the factors influencing students’ intentions to switch from conventional to Islamic banks among Islamic Banking students at UIN Sayyid Ali Rahmatullah Tulungagung. Despite the rapid growth of Islamic banking assets in Indonesia, its market share remains relatively low, highlighting the need to understand switching behavior among Generation Z. Using a sequential explanatory mixed-methods design, quantitative data were collected from 85 students through questionnaires and analyzed using multiple linear regression, while qualitative insights were obtained from interviews with 14 informants. The findings reveal that subjective norms, product knowledge, digital banking, and alternative attractiveness positively and significantly affect switching intention, with alternative attractiveness emerging as the strongest determinant. Together, these variables explain 69.7% of the variation in switching intention. Qualitative results show that switching intention develops through a sequential process in which subjective norms encourage awareness, product knowledge strengthens rational evaluation, digital banking facilitates access, and alternative attractiveness drives the final decision. The study contributes to the understanding of Islamic banking adoption among Generation Z and offers practical implications for increasing customer migration to Islamic banks.